REGIONAL DIFFERENCES IN DIRECT PAYMENTS IN POLAND AND EUROPEAN UNION - Chmielewska, Barbara (Economics of Agriculture, 2011)
Since 2004, together with the integration of Poland with the European Union, Polish agriculture has been included in the Common Agricultural Policy (CAP). This policy has changed the system of structuring the incomes of farming families. Agricultural holdings, after fulflling the conditions laid down by the law, can apply for various forms of fnancial support. In the period of the integration of Poland with the European Union the income situation of farming families has improved, mainly because of direct subsidies in conjunction with structural funds. Despite the high total amount paid annually to farmers on account of direct subsidies, a signifcant number of agricultural holdings over 1 ha have beneftted little from this form of fnancial support. These were primarily small and medium-sized holdings. Direct payments are regionally diversifed.